What does the NHS Long Term Plan mean for diabetes care?. (2nd February 2019) - Phillips, Anne
Abstract : The NHS Long Term Plan, launched in January 2019, outlined several targets and schemes to improve patient care. However, practice nurses need to be aware of what these changes might mean for their practice, particularly in diabetes care This is an exciting time of transformation and engagement in diabetes care for general practice. TheKing's Fund (2018) reported 'a shared responsibility for health' which echoes this vision for transformation in terms of diabetes care and supporting more avenues to enable people to gain the skills and knowledge to live well with their condition. Furthermore, the new NHS Long Term Plan (NHS, 2019 ) announced several initiatives for people living with diabetes, which are detailed in this article.